Investigating First-Stage Exchange Rate Pass-Through: Sectoral and Macro Evidence from Euro Area Countries - Nidhaleddine Ben Cheikh; Christophe Rault (Institute of Labor Economics (IZA), 2017)
In this paper, we evaluate the first-stage pass-through, namely the responsiveness of import prices to the exchange rate changes, for a sample of euro area (EA) countries. Our study aims to shed further light on the role of microeconomic factors vs. macroeconomic factors in influencing the extent of the exchange rate pass-through (ERPT). As a first step, we conduct a sectoral analysis using disaggregated import prices data. We find a much higher degree of pass-through for more homogeneous goods and commodities, such as oil and raw materials, than for highly differentiated manufactured products, such as machinery and transport equipment. Our results confirm that cross-country differences in pass-through rates may be due to divergences in the product composition of imports. The higher share of imports from sectors with lower degrees of pass-through, the lower ERPT for an economy will be. In a next step, we investigate for the impact of some macroeconomics factors or common events experienced by EA members on the extent of pass-through. Using the System Generalized Method of Moments within a dynamic panel-data model, our estimates indicate that decline of import-price sensitivity to the exchange rate is not significant since the introduction of the single currency. Our findings suggest instead that the weakness of the euro during the first three years of the monetary union significantly raised the extent of the ERPT. This outcome could explain why the sensitivity of import prices has not fallen since 1999. We also point out a significant role played by the inflation in the Eurozone, as the responsiveness of import prices to exchange rate fluctuations tends to decline in a low and more stable inflation environment. Overall, our findings support the view that the extent of pass-through is comprised of both macro- and microeconomic aspects that policymakers should take into account.
Keywords: E31; F31; F40; 330; exchange rate pass-through; import prices; dynamic panel data